Practitioner review: Current best practice in the use of parent training and other behavioural interventions in the treatment of children and adolescents with Attention Deficit Hyperactivity Disorder (ADHD) - Daley, David; Van Der Oord, Sakia; Ferrin, Maite; Cortese, Samuele; Danckaerts, Marina; Doepfne, Manfred; Van den Hoofdakker, Barbara J.; Coghill, David; Thompson, Margaret; Asherson, Philip; Banaschewski, Tobias; Brandeis, Daniel; et al. (Wiley, 2017)
Background: Behavioural interventions are recommended for use with children and young people with ADHD, however specific guidance for their implementation based on the best available evidence is currently lacking. Methods: This review used an explicit question and answer format to address issues of clinical concern, based on expert interpretation of the evidence with precedence given to meta-analyses of randomised controlled trials. Results: On the basis of current evidence that takes into account whether outcomes are blinded, behavioural intervention cannot be supported as a front-line treatment for core ADHD symptoms. There is however, evidence from measures that are probably blinded that these interventions benefit parenting practices and improve conduct problems which commonly co-occur with ADHD, and are often the main reason for referral. Initial positive results have also been found in relation to parental knowledge, children’s emotional, social and academic functioning – although most studies have not used blinded outcomes. Generic as well as specialised ADHD parent training approaches - delivered either individually or in groups – have reported beneficial effects. High quality training, supervision of therapists and practice with the child, may improve outcomes but further evidence is required. Evidence for who benefits the most from behavioural interventions is scant. There is no evidence to limit behavioural treatments to parents with parenting difficulties or children with conduct problems. There are positive effects of additive school based intervention for the inattentive subtype. Targeting parental depression may enhance the effects of behavioural interventions. Conclusion: Parent training is an important part of the multi-modal treatment of children with ADHD which improves parenting, reduces levels of oppositional and non-compliant behaviours and may improve other aspects of functioning. However, blinded evidence does not support it as a specific treatment for core ADHD symptoms. More research is required to understand how to optimise treatment effectiveness either in general or for individual patients and explore potential barriers to treatment uptake and engagement. In terms of selecting which intervention formats to use it seems important to acknowledge and respond to parental treatment preferences.